Translating desire : the politics of gender and culture in India - Sharma, Anjana, 1961-; Bose, Brinda (New Delhi : Katha, 2002)
On the politics of sexuality and the production of the cultural text in contemporary India.
Keywords: Sex -- Political aspects -- India; Women -- Sexual behavior -- India